2016
DOI: 10.1002/adsc.201500985
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Imidodiphosphoric Acids‐Catalyzed Friedel–Crafts Reactions of Indoles/Pyrroles with 3‐Hydroxy‐indolyloxindoles: Enantioselective Synthesis of 3,3‐Diaryloxindoles

Abstract: Thef irst enantioselective Friedel-Crafts alkylation of indoles and pyrroles with 3-hydroxy-3-indolyloxindoles to access twon ovelt ypes of 3,3-diaryloxindoles catalyzed by chiral imidodiphosphoric acids hasb een reported. Ar ange of quaternary carbon centered 3,3-diaryloxindoles were synthesized in high yield (up to > 99%) with excellent enantioselectivity (up to 98% ee)a tl ow catalyst loadings (as low as 0.5 mol%). TheF riedel-Crafts reaction between indoles and 3-hydroxy-3-indolyloxindoles is amenable to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(12 citation statements)
references
References 82 publications
(2 reference statements)
0
12
0
Order By: Relevance
“…For example, in 2010, You and co‐workers developed a substitution reaction for 3‐indolylamines with indoles, which led to chiral 3,3′‐BIMs in high yields with moderate enantioselectivities . Subsequently, Zhang's group disclosed efficient methods for the synthesis of optically active 3,3′‐BIMs, in which O ‐trimethylsilyl‐protected 3‐indolylmethanols and 3‐hydroxyindolyloxindoles were used as acceptors to react with indoles by promotion of chiral imidodiphosphoric acids (Scheme a) ,. Recently, Shi and co‐workers reported a highly efficient catalytic asymmetric arylation reaction between substituted indoles and isatin‐derived 3‐indolylmethanols .…”
Section: Methodsmentioning
confidence: 99%
“…For example, in 2010, You and co‐workers developed a substitution reaction for 3‐indolylamines with indoles, which led to chiral 3,3′‐BIMs in high yields with moderate enantioselectivities . Subsequently, Zhang's group disclosed efficient methods for the synthesis of optically active 3,3′‐BIMs, in which O ‐trimethylsilyl‐protected 3‐indolylmethanols and 3‐hydroxyindolyloxindoles were used as acceptors to react with indoles by promotion of chiral imidodiphosphoric acids (Scheme a) ,. Recently, Shi and co‐workers reported a highly efficient catalytic asymmetric arylation reaction between substituted indoles and isatin‐derived 3‐indolylmethanols .…”
Section: Methodsmentioning
confidence: 99%
“…This strategy, which again employed chiral imidodiphosphoric acids as catalysts, allowed access to a new family of 3,3diaryloxindoles 94. [69] Once optimized, the best reaction conditions involved the use of 2.5 mol% of H 8 -BINOL-derived imidodiphosphoric acid XXXV as the catalyst and 1.5 mol % of HP-β-CD (hydroxypropyl-βcyclodextrin) as an additive, in THF at 55°C. The use of β-cyclodextrin had previously been reported as a supramolecular catalyst to promote substitution reactions of indoles with isatins.…”
Section: Brønsted Acid Catalyzed Fca Reactionsmentioning
confidence: 99%
“…Shi and co‐workers found that chiral phosphoric acids could catalyse this process to give high yields, [60] although only moderate enantioselectivity was obtained in most cases. Zhang and co‐workers subsequently showed that imidodiphosphoric acid 37 is a highly efficient catalyst for this process, [61] working at low loadings (0.5 mol %), while the addition of 5 Å MS was essential for improving the enantioselectivity without compromising the reaction efficiency (Scheme 27). The reaction scope was demonstrated for substrates bearing a range of substituents within each of the benzenoid rings, while substituted pyrrole nucleophiles are also well tolerated.…”
Section: Dehydrative C−c Bond Formationmentioning
confidence: 99%